Genotyping for Blast (Pyricularia oryzae) Resistance Genes in F2 Population of Supa Aromatic Rice (Oryza sativa L.) - Kanyange, L.; Kamau, J.; Ombori, O.; Ndayiragije, A.; Muthini, M. (Hindawi Limited, 2019)
The ascomycete fungus, Pyricularia oryzae or Magnaporthe oryzae, is known to cause blast disease in more than 80 host plants of the Gramineae family—cereals including rice and grasses. The improvement of the Supa234 rice line (IR97012-27-3-1-1-B, containing badh2 gene for aroma) developed at IRRI-ESA Burundi consisted of introgression of R genes (Pita and Pi9) for blast resistance. The F2 population obtained via the cross had been screened for blast resistance using inoculation with Pyricularia oryzae spore’s suspension. The objectives of this study were to assess the presence of Pita and Pi9 genes for blast resistance and to assess the presence of the badh2 gene for aroma in the screened F2 plants using molecular markers. Genotyping was carried out in 103 F2 plants which grew to maturity using the KASP genotyping method with SNP markers (snpOS0007, snpOS0006, and snpOS0022) targeting the Pita and Pi9 genes for blast resistance and the badh2 gene for aromatic fragrance. The genotyping results showed that 38 F2 plants had the Pita gene present in both alleles, 31 F2 plants with the Pita gene in one allele, and only one plant (3B1) was found with the Pi9 gene in one allele. The badh2 gene for aroma was detected in 27 F2 plants on both alleles and in 57 F2 plants on one allele. There were thirteen plants which had both the Pita gene and the badh2 gene for aroma, and only one plant (3B1) had a combination of the three genes (Pita, Pi9, and badh2). Seven plants resistant to blast disease (2H2, 2H4, 1G2, 1C12, 1E13, 1B12, and 1C5) with the Pita and badh2 genes were found, and only one resistant plant (3B1) had a combination of the three genes Pi9, Pita, and badh2 which is recommended to be bulked for the development of the Supa aromatic rice variety resistant to blast disease. The plants generated by the best line 3B1 should further be evaluated for grain quality (Supa type) after F5 generation in the field.